Monologue performance using West Java folklore: can it improve high school students' speaking skills? - Repelita, Tridays; Jamaludin, Ujang; Leksono, Suroso Mukti (Panicgogy International Journal, 2023)
The purpose of this study was to analyze the improvement of high school students' speaking skills in a private school in Karawang Regency through monologue performances using West Javanese stories. The research design used was a classroom action research design, through stages consisting of planning, implementing action, observing, and reflecting. The research data is in the form of process data and learning outcomes of speaking skills. The research results show that 50% of student activity in cycle I is in the inactive category. The observation results obtained were that student activity in cycle II increased more than cycle I where the average student activity score was 84% ​​which was in the active category. on the monologue performance test cycle I, out of 15 students, 5 students or (33%) passed in the good category, in the less category <65 there were 10 students or (67%), then in the sufficient category the average score was 65-71 achieved by 0 students or (0%) with an average value of cycle one is 56%. In cycle II, out of 15 students, 12 students or (81.4%) passed in the good category, in the less category <65 there was 1 student or (6.6%), then in the sufficient category the average score was 65-71 achieved by 2 students or (12%) with an average value of cycle II is 81%. As a suggestion to improve students' speaking skills, it is hoped that teachers can apply monologue performances as an alternative in learning Indonesian. Keywords: monologue, folklore, speaking ability, senior high school